Seismic Vulnerability Microzonation Using Hvsr Method in Kalisalak Hamlet, Garunglor Village, Sukoharjo Sub-District, Wonosobo District - Adam Ardiansyah; Aryono Adhi; Nugroho Budi Wibowo; SARWI; Budi Astuti; Cindiwati (Universitas Negeri Semarang, 2024)
Kalisalak Hamlet in Sukoharjo District is faced with the risk of landslides that can affect the structure of residents' houses. This study aims to identify potential landslide zones based on the parameters of Dominant Frequency (f_0), Amplification Factor (A_0), and Seismic Vulnerability (K_g)to determine areas that are potentially vulnerable to landslides. Microseismic measurements were carried out at 25 measurement points in the landslide zone. Measurements used a 3-component digital portable seismograph (North-South, West-East, and Vertical). Microseismic data were processed using Geopsy software with the HVSR (Horizontal-to-Vertical Spectral Ratio) method to obtain an H/V curve that provides Dominant Frequency (f_0) and Amplification Factor (A_0) values. The results showed that Kalisalak Village has a dominant frequency value between 3 Hz to 12.5 Hz and an amplification factor value between 1.4 to 6.8. This variation indicates that some areas are more susceptible to seismic vibration amplification. Based on the Dominant Frequency (f_0) value and Amplification Factor (A_0), a Seismic Vulnerability (K_g) microzonation map was created for Kalisalak hamlet with a value range of 0.2 to 7 with a high vulnerability value located in the landslide area south of the village. This map is important for disaster mitigation planning in Kalisalak hamlet.